2020
DOI: 10.1111/mcn.13072
|View full text |Cite
|
Sign up to set email alerts
|

Infant feeding practices and sleep at 1 year of age in the nationwide ELFE cohort

Abstract: Sleep problems reported by parents affect 20% to 30% of infants. Few studies focused on the longitudinal association between infant feeding practices and sleep, especially in France. Analyses were based on 8,696 infants from the French national birth cohort ELFE. Collection of feeding practices from birth to 10 months allowed for the identification of trajectories of use of baby cereals and thickened formula by group‐based trajectory modelling and calculation of duration of any breastfeeding (BF) and age at co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 44 publications
(78 reference statements)
1
4
0
Order By: Relevance
“…This study also demonstrated that infant feeding problems triple the likelihood of sleeping problems. This finding is consistent with the findings of Messayke et al (2021), who discovered that early initiation of baby cereals, thickened formula, and breastfeeding over six months are associated with poor sleep [ 53 ]. Field (2017) also ascribed that feeding problems are factors associated with isolated infant sleeping problems [ 54 ].…”
Section: Discussionsupporting
confidence: 92%
“…This study also demonstrated that infant feeding problems triple the likelihood of sleeping problems. This finding is consistent with the findings of Messayke et al (2021), who discovered that early initiation of baby cereals, thickened formula, and breastfeeding over six months are associated with poor sleep [ 53 ]. Field (2017) also ascribed that feeding problems are factors associated with isolated infant sleeping problems [ 54 ].…”
Section: Discussionsupporting
confidence: 92%
“…Many mothers responded that they are co-sleeping (defined in this study as bedsharing): there is a difference in reactive co-sleeping due to necessity of limited sleep spaces, versus intentional co-sleeping to promote attachment [ 27 , 29 ]. Pediatricians should ask “Do you have a crib for her to sleep?” More mothers acknowledged co-sleeping in interviews than in surveys; perhaps theyknew this went against pediatrician recommendations [ 20 ], or perhaps they responded as to their intent at the start of the night rather than the reality of responding to night waking. Well-intentioned pediatricians may ask unhelpful leading questions; for example: “He always sleeps in his own crib, right?”.…”
Section: Discussionmentioning
confidence: 99%
“…Pediatricians should ask "Do you have a crib for her to sleep?" More mothers acknowledged cosleeping in interviews than in surveys; perhaps theyknew this went against pediatrician recommendations [20], or perhaps they responded as to their intent at the start of the night rather than the reality of responding to night waking. Well-intentioned pediatricians may ask unhelpful leading questions; for example: "He always sleeps in his own crib, right?".…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations